Strategy to Improve the Digital Reading House - Budiman Budiman; Ewin Sanjaya Gajah; Liza Handayani Batu Bara (Edumaspul: Jurnal Pendidikan, 2023)
This research is entitled strategies for increasing digital reading houses. The aim of this research is to look for various strategies that can be used to improve digital reading houses that can be used for the general public and especially for students as an effort to increase student reading literacy. Reading houses will be an alternative for reading digitally. This research uses a qualitative phenomenological method. The phenomena discussed in this research are the obstacles and challenges in improving digital reading houses and effective strategies used to improve digital reading house strategies. The results of this research state that there are six functions that must be carried out simultaneously to improve the digital reading house. The results of this research can then be analyzed to answer research questions, namely the challenges of digital reading houses, how to increase reading interest with digital reading houses, and strategies for improving digital reading houses. The conclusion of this research is that there are various challenges faced in improving digital reading houses. This challenge can be faced with various strategies, namely by offering free access to various types of reading materials that have been adapted to age and interests, activating reading communities, providing rating and review pages.